The Function of Problem and Reflective Recurrence in Historical Theology - Mohammad Hasan Ahmadi (تاریخ اسلام)
If Fiqh ol-Ravayeh like Fiqh ol-Hadith is regarded in the array of sciences on the analysis of historical reports, it can be designated as one of the bases of analytical history. Conversely, the analysis of historical reports related to the historical theology has not yet made methodical and systematic. Considering the category of method in the domain of historical theology and putting emphasis on the reports related to histories such as the history of Quran, the history of hadith, and the history of interpretation, this article tries to propose a new method of historical analysis as a reflective analysis method. In this method which is based on the reflection of historical report in the external space, the initiation of problem principle signifying the amount of non-resolvability of the status of statement of report on status over the statement of report and the principle of reflective recurrence as the opposite of problem provides the more accurate ground towards the analysis of historical reports. The administration of these two principles is an obstacle towards false interpretation and fallacy in the historical analysis and it strengthens the historical reasoning.